Facile synthesis of superparamagnetic Fe3O4 nanoparticles just using ferric citrate and water. Issue 176 (21st November 2016) - Xu, Yaohui; Wang, Tonghui; Sun, Dongfeng; Li, Ruixing
ABSTRACT: Fe3 O4 nanoparticles were synthesized by a facile one-pot hydrothermal process just using ferric citrate and water without any additional reagent and post-treatment. The temperature of hydrothermal reaction had important influence on the crystallinity and magnetic property of Fe3 O4 samples. Fe3 O4 sample synthesized at 200 °C for 24 h showed a narrow size distribution (4 to 8 nm in diameter), and exhibited apparent superparamagnetism with saturated magnetization of 55.1 emu/g. The narrow size distribution and superparamagnetism were the interesting features of these Fe3 O4 nanoparticles.